Dignity of a Person in Hospital Pyjamas. Individual Approach as a Basis for Respect - Małgorzata Wałejko (Nicolaus Copernicus University in Toruń, 2017)
The text is a pedagogical response to depersonalization of people in a serious clinical state, elderly and/or chronically ill, frequently severely ill, staying in hospitals or total care facilities. Specific nature of hospital conditions ('pyjamas'), addressing a patient in the second person singular, refraining from a dialogue and depriving patients of the possibility to make basic choices contribute to isolation among patients and the feeling of losing their centrality. While referring to major metaphysical qualities of a personal being, the author marks possible ways of saving the sense of individualism among people who depend on care provided by others, which is the intellectual and volitional (self-)education. In the case of people who remain unconscious, an adequate and personalistic attitude involves building a community based on presence of two entities as a sufficient condition to develop a relationship in the meaning of the personalistic norm.